V.A.C VERAFLO CLEANSE CHOICETM therapy for a chronic non-healing foot wound after ray amputation for gangrene of the big toe. Issue 1 (2019) - Tay, Luke Hsien Tsung; Yap, Hao Yun; Lee, Shaun Qing Wei; Loh, Wei Liang; Chng, Siew Ping
No abstract available